On a non-self adjoint expansion formula. (1984) - Naylor, D.
Abstract : This paper develops a formula of inversion for an integral transform of the kind similar to that associated with the names of Kontorovich and Lebedev except that the kernel involves the Neumann functionY u ( k r ) and the variabler varies over the infinite intervala ≤ r < ∞ wherea > 0 The transform is useful in the investigation of functions that satisfy the Helmholtz equation and a condition of radiation at infinity. The formula established is expressed entirely in terms of series expansions and replaces earlier inversion formulas that require the evaluation of contour integrals.